(untitled) (Global Journal of Computer Science and Technology, 2024)
The aim of this study is to create and incorporate signature character for a mass market organic apparel brand in the collection of Spring summer 2021 for the age group of 0-2 years and to implement this character in all other trims packages name tags and carton boxes promotion posters flyers banners or other products used for the brand This study focusses mainly on sustainable fashion and the need of comfort for infants wear Detailed research was executed to know the preference of the parents towards the new character developed and their application onto various mediums Samples were developed for eccentric silhouettes and new designs as per the theme chosen and designs are shown in the methodology